2016
DOI: 10.1016/j.joto.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular-evoked myogenic potentials in miniature pigs

Abstract: ObjectiveTo report detection of vestibular-evoked myogenic potentials (VEMPs) in the miniature pig.MethodsPotentials evoked by 1000 Hz tone bursts were recorded from neck extensor muscles and the masseter muscles in normal adult Bama miniature pigs anesthetized with 3% pentobarbital sodium and Carbachol II.ResultsThe latency of the first positive wave P from neck extensor muscles was 7.65 ± 0.64 ms, with an amplitude of 1.66 ± 0.34 uv and a rate of successful induction of 75% at 80 dB SPL. The latency of poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Negishi-Oshino et al used neck extensor muscle cVEMPs, in addition to behavioral rotarod, beam crossing, and air-righting reflex tests in adult C57BL/6J mice to measure IDPN vestibulotoxicity and thereby create an in vivo model of adult mammalian vestibular dysfunction ( 47 ). Finally, neck extensor muscle VEMPs have been studied in mini-pigs and rats ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Negishi-Oshino et al used neck extensor muscle cVEMPs, in addition to behavioral rotarod, beam crossing, and air-righting reflex tests in adult C57BL/6J mice to measure IDPN vestibulotoxicity and thereby create an in vivo model of adult mammalian vestibular dysfunction ( 47 ). Finally, neck extensor muscle VEMPs have been studied in mini-pigs and rats ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Negishi-Oshino et al used neck extensor muscle cVEMPs, in addition to behavioral rotarod, beam crossing, and airrighting reflex tests in adult C57BL/6J mice to measure IDPN vestibulotoxicity and thereby create an in vivo model of adult mammalian vestibular dysfunction (47). Finally, neck extensor muscle VEMPs have been studied in mini-pigs and rats (48,49). On post-SSCD day 1 in the small (1 mm) group, there was a small increase in latency, and the amplitude of the c+VEMP response was greatly decreased along with an increase in the stretch reflex.…”
Section: Imagingmentioning
confidence: 99%
“…Masseter VEMP showed noticeably lower amplitudes when compared to cVEMP in both EMG-scaled and unscaled conditions. Studies on animals have also reported similar findings where the VEMPs recorded from neck extensor muscles exhibited higher amplitudes as compared to those recorded from the masseter muscle, while the latencies remained similar (Shi et al 32 ). The discrepancy in the peak-to-peak amplitude of cVEMP and mVEMP in the present study could have resulted due to the inherent difference in muscle mass between the masseter muscle and This article is protected by copyright.…”
Section: Accepted Manuscriptmentioning
confidence: 61%
“…For the VEMP test, pigs were anesthetized with 3% pentobarbital sodium (1 ml/kg) and Sumianxin II (0.1 ml/kg). As the masseter muscles are easier to be surgically exposed than the neck extensor muscles, we recorded the response of masseter muscles for VEMP test [21]. VEMP response was elicited by open field sound stimuli.…”
Section: Methodsmentioning
confidence: 99%